(untitled) (Revista NUPEART, 2023)
The teaching of dance, as a methodology for teaching body studies for teaching the arts, can break with colonial structural logic. The pedagogy of the oppressed and the “bixa” ethics are adhered to, concomitantly, as beacons of the praxis of the artistteacher, understood as being in a constant process of updating their practices – methodological, pedagogical, didactic and artistic – through a neologism : “professendo” (being a professor). Unconcluded, the professor seeks, through reflection on his practices, to abolish these logics that materialize in educational processes that deal with authoritarianism, adoption of universal models, contents taught in a banking education mode and hierarchical relations, both in the choice of contents and in the verticality of treatment between educator-student. The premise is that a colonial logic that structures dance teaching nowadays deals mainly with the notion that the educator knows everything and the student knows nothing, emptying the creative power and the full development of the subject as a critical citizen through silencing discipline. It is indicated that dance professionals in the country are (in)trained in these structuring colonial logics present in dance teaching, especially in classical ballet. A methodological and content proposal for teaching planned dance as a practice of freedom is presented. The counterpoint that breaks with these logics presupposes dialogic acts in the practices of the artistteacher - a “professendo” (being a professor), - who adheres to a project of search for equality and inclusion of subjects in education and art.